Foreign policy at the turn of the epochs. Book review of ‘History of the Soviet foreign policy in 1918–1941’ by O.R. Airapetov - A. A. Vershinin (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика, 2025)
This review examines ‘History of the Soviet foreign policy in 1918–1941’, the monograph by O.R. Airapetov, published in 2024. To date, it represents one of the most detailed studies of Soviet foreign policy during the interwar period.Building on a vast historiography, both domestic and foreign, and using a variety of sources, the author covers a wide range of issues, accompanying the emergence of the Soviet Union on the world map and its transformation into a key international actor. The author identifies four stages in this process: 1917–1922 (the period of the Civil War and Allied Intervention), 1920s — early 1930s (the formation of the Soviet foreign policy, marked by a series of international crises), early 1930s — 1939 (the USSR’s struggle against the military danger in Europe and its participation in the collective security system), 1939–1941 (the preparation of the USSR for a military clash with Germany). A distinctive feature of the monograph under review is its deep contextualization of the considered phenomena and events. In this regard, the reviewer notes that the subject matter is not so much the foreign policy activities of the People’s Commissariat for Foreign Affairs as the Soviet Union’s ‘grand strategy’, embracing diplomacy as only one of the tools along with economy, military planning and intelligence work. In his work, the author airs a number of views unconventional for Russian historiography, arguing, in particular, that the USSR in the 1920s and 1930s was only underway to claim the great power status, without being recognized as such at the international level and without having a corresponding leverage on global developments. Another important idea is a critical assessment of M.M. Litvinov’s activities as the People’s Commissar for Foreign Affairs. The reviewer shares this opinion and argues that during the pre-war decade, the People’s Commissariat for Foreign Affairs overrated the potential of the collective security policy and the possibility of its alignment with the Soviet national interests. As this contradiction became evident, M.M. Litvinov’s political and administrative positions shed, which eventually led to his resignation in 1939. In conclusion, the reviewer notes that the period considered in the monograph was crucial for establishing a new Russian/Soviet foreign policy strategy, and therefore deserves further reflection within academic community.